The Acquisition of English Definite Article “the” by Mandarin and Indonesian Speakers - Rio Januara N. Yahman; Wenyi Zang; Wanting Zhu (International Journal in Applied Linguistics of Parahikma, 2021)
By replicating Feng (2019) with some modifications, this study aimed to identify the acquisition pattern of two kinds of English definiteness, anaphoric and non-anaphoric. Being a language without article system, Mandarin Chinese employed demonstrative determiners to function as definite article and shared the same features as English definite article “the”. In the current study, the participants were 3 L1-Chinese and 3 L1-Indonesian L2-English learners, who engaged in an Acceptability Judgement Task (AJT) and a post-task interview. Align with Feng’s finding, this study revealed that Chinese participants encountered less difficulties than their Indonesian counterparts in the use of ‘the’, as a possible result of L1 transfer; and that Chinese participants underperformed in bridging conditions, indicating the challenge of presupposition at the semantics-pragmatics interface.